Sword handling: the early christian reception of Matthew 10:34 - Croy, N. Clayton (Journal of the bible and its reception, 2019)
The saying of Jesus in Matt 10:34 that he has “not come to bring peace, but a sword,” seems at odds with the general tenor of his life and teachings. Some proponents of a revolutionary Jesus have seized upon this saying as evidence that he was sympathetic to, and perhaps even supportive of, violent revolution. This article surveys patristic commentary on this verse from the first few centuries to see how this “hard saying” was understood and handled. Although a small number of writers expressed unease about the imagery and the perceived contradiction with other texts of scripture, the general trend was to construe the “sword” metaphorically, usually by appealing to a variety of passages containing the same word. No patristic writer understood the saying as an endorsement of violence, even those whose socio-political context might have justified it. Finally, although some of the hermeneutical strategies of the Fathers may not be embraced by modern exegesis, they often produced readings that were culturally and religiously sensitive as well as rhetorically insightful.